Team leadership in community colleges - Boggs, George R.; McPhail, Christine Johnson (Stylus, 2020)
"This edited collection is the first book to address the topic of how leaders work with teams to manage and transform community colleges. There is a need to develop better leadership teams in order to administer community colleges effectively and to improve these organizations, whether it be an individual campus, multi-college system or state-wide organization. Edited by two long-time leaders in the field, the book includes contributions from many other experienced leaders and scholars of community colleges"--